2020
DOI: 10.1155/2020/3732718
|View full text |Cite
|
Sign up to set email alerts
|

Bakuchiol Alleviates Hyperglycemia-Induced Diabetic Cardiomyopathy by Reducing Myocardial Oxidative Stress via Activating the SIRT1/Nrf2 Signaling Pathway

Abstract: Bakuchiol (BAK), a monoterpene phenol reported to have exerted a variety of pharmacological effects, has been related to multiple diseases, including myocardial ischemia reperfusion injury, pressure overload-induced cardiac hypertrophy, diabetes, liver fibrosis, and cancer. However, the effects of BAK on hyperglycemia-caused diabetic cardiomyopathy and its underlying mechanisms remain unclear. In this study, streptozotocin-induced mouse model and high-glucose-treated cell model were conducted to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 59 publications
0
44
1
Order By: Relevance
“…This evidence pointed out that the promotion of the PGC1/Nrf2 signaling pathway accompanied by the occurrence of mitophagy was to eliminate the ROS-induced oxidative damage. However, the results were not consistent with the previous studies that proved the promotion of autophagy and the Nrf2-PGC1-Sirt1 signaling pathway accompanied by the attenuation of ROS in retinal degeneration [31,32,57]. Accumulating evidence has shown that Sirt1 plays a crucial role in cardiac protection in various cardiovascular diseases through a complex signaling network, including autophagy [58] and apoptosis [59].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This evidence pointed out that the promotion of the PGC1/Nrf2 signaling pathway accompanied by the occurrence of mitophagy was to eliminate the ROS-induced oxidative damage. However, the results were not consistent with the previous studies that proved the promotion of autophagy and the Nrf2-PGC1-Sirt1 signaling pathway accompanied by the attenuation of ROS in retinal degeneration [31,32,57]. Accumulating evidence has shown that Sirt1 plays a crucial role in cardiac protection in various cardiovascular diseases through a complex signaling network, including autophagy [58] and apoptosis [59].…”
Section: Discussioncontrasting
confidence: 76%
“…PGC-1α was positively regulated by Sirt1, which is linked to autophagy [30]. Previous studies have also shown that Sirt1 can regulate mitochondrial ROS levels by deacetylating SOD2 [31]. Numerous studies have also clearly indicated that Sirt1 can exert antioxidative effects via the activation of Nrf2 [32].…”
Section: Introductionmentioning
confidence: 95%
“…Activation of the SIRT1/Nrf2 signaling pathway has been reported to promote the production of antioxidant. 39 , 40 Furthermore, regular exercise can stimulate the activation of Nrf2 to enhance the endogenous antioxidant ability to resist the destructive effect of reactive oxygen species. 20 Therefore, we explored the expression of Nrf2 and its downstream cytoprotective proteins through Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gao et al found that long ncRNA (lncRNA) HOX transcript antisense RNA (HOTAIR) and Sirt1 were downregulated but miR-34a was upregulated in diabetic hearts and HG-stimulated H9c2 cells, while overexpression of lncRNA HOTAIR protected against DCM via increasing Sirt1 expression by sponging miR-34a (39). Furthermore, the Sirt1/NRF2 pathway was shown to play a role in improving DCM via alleviating myocardial oxidative stress (40). However, whether NRF2 can be regulated by the lncRNA HOTAIR/miR-34a/Sirt1 pathway in the treatment of DCM needs to be further explored.…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%